Novaluron impairs the silk gland and productive performance of silkworm Bombyx mori (Lepidoptera: Bombycidae) larvae. (January 2020) - Santorum, Marilucia; Costa, Rose Meire; dos Reis, Gustavo Henrique; Carvalho dos Santos, Daniela
Abstract: This study investigates the effects of the insect growth regulator Novaluron on the silk gland (SG) and silk cocoon production in a nontarget insect, the silkworm Bombyx mori, which is a model research insect among Lepidoptera and of great economic importance for the commercial production of silk threads. Larvae were segregated into experimental groups: the control group (CG) and the treatment group (TG), which was exposed to a Novaluron concentration of 0.15 mL/L. Following exposure, we analyzed the cytotoxic effects on the epithelial cells of the anterior, middle and posterior regions of the SG of B. mori larvae in the 3rd, 4th, and 5th instars, as well as the quality of the cocoons from larvae in the 5th instar. Cytotoxic effects were observed in the TG, such as the dilation of cells, emission of cytoplasmic protrusions, extreme rarefaction of the cytoplasm and nuclei, dilation of the endoplasmic reticulum, intracellular and intercellular spaces, spacing between the epithelial cells and the basal lamina and detachment of some cells towards the lumen of the SG, and decreased protein in the lumen, with faults in its composition. In addition, we verified ultrastructural changes in the production of fibers and silk cocoons, including a reduction in the weight of the cocoons constructed by both males and females in the TG and the construction of defective cocoons. Novaluron exposure impairs the SG and may affect the physiological functions of this organ; additionally, it compromises the quality of silk cocoons, potentially causing serious damage to sericulture. Graphical abstract: Image 108751 Highlights: We investigated the negative impacts of Novaluron on silk production of B. mori. Novaluron impaired the development of silk gland and the production of silk cocoons by B. mori. Novaluron caused cytotoxic effects to the three regions of the silk gland. Novaluron resulted faults in the deposition of silk proteins in the lumen of the silk gland. Novaluron induced decreased cocoon weight and in the quality of cocoons.